2016
DOI: 10.1371/journal.pone.0163534
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Methylation of MGMT Promoter in HNSCC: A Meta-Analysis

Abstract: BackgroundO6-methylguanine-DNA methyl-transferase (MGMT) gene, a DNA repair gene, plays a critical role in the repair of alkylated DNA adducts that form following exposure to genotoxic agents. MGMT is generally expressed in various tumors, and its function is frequently lost because of hypermethylation in the promoter. The promoter methylation of MGMT has been extensively investigated in head and neck squamous cell carcinoma (HNSCC). However, the association between the promoter methylation of MGMT and HNSCC r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
(23 reference statements)
1
7
0
Order By: Relevance
“…In addition, it has been reported that MGMT gene expression in normal and neoplatic tissues varies and MGMT promoter methylation was associated with better suvivial in some cancer types but not all 47 . In the present study, we showed that MGMT promoter methylation status was significantly associated with an increased risk of breast and gynecologic cancers, which is consistent with previous studies in head and neck squamous cell carcinoma, lung cancer, glioblastoma, and esophageal cancer 9 11 . These works including ours highlighted the possibility of using MGMT promoter methylation status as a biomarker 49 , based on the facts that MGMT promoter hypermethylation could occur early in the neoplastic process before the clinical manifestation 29 , 50 , 51 , or turn up in normal appearing tissues close to tumors 52 , 53 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, it has been reported that MGMT gene expression in normal and neoplatic tissues varies and MGMT promoter methylation was associated with better suvivial in some cancer types but not all 47 . In the present study, we showed that MGMT promoter methylation status was significantly associated with an increased risk of breast and gynecologic cancers, which is consistent with previous studies in head and neck squamous cell carcinoma, lung cancer, glioblastoma, and esophageal cancer 9 11 . These works including ours highlighted the possibility of using MGMT promoter methylation status as a biomarker 49 , based on the facts that MGMT promoter hypermethylation could occur early in the neoplastic process before the clinical manifestation 29 , 50 , 51 , or turn up in normal appearing tissues close to tumors 52 , 53 .…”
Section: Discussionsupporting
confidence: 93%
“…The hypermethylation of CpG islands is relatively rare in normal cells, thus the detection of methylated DNA in bodily fluids can be promising 8 . Several studies have focused on this in other cancers including head and neck squamous cell carcinoma, lung cancer and esophageal cancer 9 11 . Nevertheless, for breast and gynecologic cancers, although many studies have explored the association between their risks and MGMT promoter hypermethylation, the results remain inconsistent 12 – 39 .…”
Section: Introductionmentioning
confidence: 99%
“…MGMT encodes an adduct repair enzyme of O 6 -methylguanine generated by the interaction of DNA with alkylating agents present, for example, in cigarette smoke (Christmann and Kaina, 2012). The MGMT promoter methylation can reduce the protein expression having therefore oncogenic potential (Cai et al, 2016). Although our report is not the first to point out the prognostic value of MGMT for HNSCC patients, there is no consensus among studies previously published.…”
Section: Discussionmentioning
confidence: 77%
“…The gene MGMT (O6-methylguanine-DNA methyltransferase) is related to DNA repair, and increased methylation in its promoter has been reported in HNSCC (Koutsimpelas et al 2012;Chaisaingmongkol et al 2012;Dvojakovska et al 2018). In a meta-analysis based on 20 studies, the promoter of MGMT was hypermethylated in HNSCC compared to healthy controls, suggesting a connection between higher methylation and an increased risk of head and neck cancer (Cai et al 2016). Metaanalysis of OSCC cases also confirmed higher methylation in this promoter (Don et al 2014) and in addition, the increased methylation was connected with a lower level of MGMT protein (Koutsimpelas et al 2012).…”
mentioning
confidence: 99%